Interplay between the oxidation process and cytotoxic effects of antimonene nanomaterials - Congost Escoin, Pau (2024)
Pnictogen nanomaterials have recently attracted researchers’ attention owing to their promising properties in the field of electronic, energy storage, and nanomedicine applications. Moreover, especially in the case of heavy pnictogens, their chemistry allows for nanomaterial synthesis using both top-down and bottom-up approaches, yielding materials with remarkable differences in terms of morphology, size, yield, and properties. In this study, we carried out a comprehensive structural and spectroscopic characterization of antimony-based nanomaterials (Sb-nanomaterials) obtained by applying different production methodologies (bottom-up and top-down routes) and investigating the influence of the synthesis on their oxidation state and stability in a biological environment. Indeed, in situ XANES/EXAFS studies of Sb-nanomaterials incubated in cell culture media were carried out, unveiling a different oxidation behavior. Furthermore, we investigated the cytotoxic effects of Sb-nanomaterials on six different cell lines: two non-cancerous (FSK andHEK293) and four cancerous (HeLa, SKBR3, THP-1, and A549). The results reveal that hexagonal antimonene (Sb-H) synthesized using a colloidal approach oxidizes the most and faster in cell culture media compared to liquid phase exfoliated (LPE) antimonene, suffering acute degradation and anticipating well-differentiated toxicity from its peers. In addition, the study highlights the importance of the synthetic route for the Sb-nanomaterials as it was observed to influence the chemical evolution of Sb-H into toxic Sb oxide species, playing a critical role in its ability to rapidly eliminate tumor cells. These findings provide insights into the mechanisms underlying the dark cytotoxicity of Sb-H and other related Sb-nanomaterials, underlining the importance of developing therapies based on controlled and on-demand nanomaterial oxidation.